Agent-Based Urban Growth Simulation A Case Study on Istanbul - Bingol, Cemal Koray; Colakoglu, Birgul (ECAADE-EDUCATION & RESEARCH COMPUTER AIDED ARCHITECTURAL DESIGN EUROPE, 2016)
This study aims to create a simulation model for urban growth with agent-based modeling. The model is based on the theoretical research of Michael Batty on urban growth simulations. The study explains how the theoretical approach applied in the model with the parameters. The model in this study is created in an open-source API called 'Processing' and the simulations executed through the parameters in the study. The results of the simulation are compared with each other to find optimal parameters fits in the theoretical approach. Parameters are tested on an existing urban settlement map, which Is Istanbul. The results of Istanbul simulation are compared with existing density and urban sprawl maps of Istanbul and discussed for further studies.
Keywords: agent-based design; urban growth; urban simulation; Architecture; Computer Science